Синтез и исследование некоторых превращений (пиридил-3) замещенных 1,2,4-триазол-3- и 1,3,4-тиадиазол-5-тиолов - Т. Р. Овсепян; С. В. Диланян; Н. С. Минасян; Р. Г. Мелик-Оганджанян (ՀՀ ԳԱԱ հրատ.)
В поисках новых биологически активных соединений на основе гидразида никотиновой кислоты синтезированы (пиридил-3)замещенные 1,2,4-триазол-3- и 1,3,4-тиадиазол-5-тиолы и изучены их реакции N-аминометилирования, цианэтилирования и S-алкилирования галогенидами, содержащими различные фармакофорные группы. Նոր կենսաբանորեն ակտիվ միացությունների ստեղծման համար նիկոտինաթթվի հիդրազիդի հիմքի վրա սինթեզված են (պիրիդիլ-3)տեղակալված 1,2,4-տրիազոլ-3- և 1,3,4-թիադիազոլ-5-թիոլներ և ուսումնասիրված են նրանց N-ամինոմեթիլացման, ցիան-էթիլացման, ինչպես նաև տարբեր ֆարմակաֆոր խմբեր պարունակող հալոգենիդներով S-ալկիլացման ռեակցիաները: For synthesis of new biologically active compounds based on the nicotinic acid hydrazide a series of new (pyridil-3)substituted1,2,4-triazole-3- and 1,3,4-thiadiazole-5-thiols have been synthesized and their N-aminomethylation, cyanethylation, as well as alkylation reactions with different halides have been studied. The intramolecular nucleophilic S-O rearrangement of the S-alkylated product from the reaction of 5-(pyridyl-3)-4-phenyl-4H-1,2,4-triazole-3-thiole with ethylenechlorohydrin was described, and the possible mechanism of the reaction was reported.
Keywords: Organic Chemistry